Leader sequences of murine coronavirus mRNAs can be freely reassorted: evidence for the role of free leader RNA in transcription. - Makino, S (1986)
Mouse hepatitis virus (MHV), which replicates in cytoplasm of infected cells, contains an identical leader RNA sequence at the 5' end of each of the virus-specific mRNAs. Previous studies suggested that the synthesis of these mRNAs does not involve conventional RNA splicing and may instead require priming by a free leader RNA. In this communication, we demonstrate that, during a mixed infection with two different MHVs, the leader RNA sequences from one virus could be detected on the mRNAs of the coinfecting virus at a high frequency, as if the leader sequence and mRNAs were joined together from two randomly segregating RNA segments. This finding demonstrates that MHV mRNA transcription utilizes independently transcribed leader RNA species that possess the trans-acting property. This study thus provides further evidence in support of the unique model of "leader-primed transcription" for coronavirus mRNA synthesis.